The palynology of tertiary sediments from a palaeochannel in Namaqualand, South Africa. - de Villiers, S. E.; Cadman, A. (Bernard Price Institute for Palaeontological Research, 1997)
A site in amaqualand, Western Cape Province, has yielded a diverse and well-preserved pa lynoflora. The site consists of a quarry, exposing a palaeochannel containing fluviatile sands, silts and clays with accompanying peat horizons. This paper presents a qualitative account of the pollen and pore assemblages extracted from the peats. Ang iosperms were dominant both in terms of the number of individuals and the recognised types. Identification were made where possible with reference to published illustrations and descriptions. There was a total of 69 palynomorph types, including spores, gymnosperm and angiosperm pollen.
Main article
Keywords: Namaqualand, Tertiary, palynology